Microstructure and mechanical properties of submerged arc welded medium-thickness Q690qE high-strength steel plate joints - Huang Wen; Qi Kai; Liu Zhigang; Yang Liang; Xue Zheyan; Li Taotao; Zhang Xiaoqiang; Li Ruifeng (High Temperature Materials and Processes)
Submerged arc welding method was used to weld 40 mm thickness Q690qE high-strength steel to study the influence of welding heat input on the microstructure and properties of Q690qE joints. The result shows that welded seam with full penetration and no obvious defects is achieved in the Q690qE joints when the welding heat input ranges from 22.5 to 33.6 kJ·cm−1. The microstructure of welded seam mainly consists of acicular ferrite and granular bainite (GB), the microstructure in coarse-grain zone is GB and lath martensite. As the welding heat input increases, the microstructure of coarse-grain zone becomes lath bainite (LB) and a small amount of GB and the microhardness decreases. The microstructure of the fine-grained area mainly includes ferrite, GB, and a small quantity of LB. In terms of impact toughness, with the heat input increasing, the impact toughness at the center of welded seam and the heat-affected zone decreases subsequently. The tensile test results of the welded joints show that the fracture always occurs in the parent material area, with a tensile strength higher than 864 MPa, and the elongation after fracture decreases as the heat input increases.